2018
DOI: 10.1002/lno.11079
|View full text |Cite
|
Sign up to set email alerts
|

Caught in broad daylight: Topographic constraints of zooplankton depth distributions

Abstract: For visual predators, sufficient light is critical for prey detection and capture. Because light decays exponentially with depth in aquatic systems, vertical movement has become a widespread strategy among zooplankton for avoiding visual predation. However, topographical features such as seamounts have been shown to block their descent, trapping them in illuminated waters with potential feeding benefits for visually searching fish.Here, we present an extensive and previously unpublished dataset on the vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…8; Table 3). Region-specific studies have also shown that diapausing Calanus tends to be found deeper and more dispersed with increased bottom depth and closer to the sea bottom at shallower locations (Dupont and Aksnes, 2012;Aarflot et al, 2018;Krumhansl et al, 2018). Our study suggests that on a pan-arctic scale, diapausing Calanus populations are blocked by shallow topography-creating potential feeding hotspots for zooplanktivores (Aarflot et al, 2018).…”
Section: Associations With Bottom Depth and Latitudesupporting
confidence: 56%
See 3 more Smart Citations
“…8; Table 3). Region-specific studies have also shown that diapausing Calanus tends to be found deeper and more dispersed with increased bottom depth and closer to the sea bottom at shallower locations (Dupont and Aksnes, 2012;Aarflot et al, 2018;Krumhansl et al, 2018). Our study suggests that on a pan-arctic scale, diapausing Calanus populations are blocked by shallow topography-creating potential feeding hotspots for zooplanktivores (Aarflot et al, 2018).…”
Section: Associations With Bottom Depth and Latitudesupporting
confidence: 56%
“…Nevertheless, both species are found deeper in winter than in summer, and the increase in WMD with bottom depth suggests that individuals seek out deep diapause habitat. In deep areas, suitable diapause habitat is available over a broad depth range, while in shallow shelves, Calanus is topographically blocked in winter (Genin, 2004;Aarflot et al, 2018). Furthermore, our pan-arctic analysis shows that C. hyperboreus descends deeper than its smaller congener in winter, possibly due to a higher size-selective predation pressure.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Another variable that could be considered in future studies is light availability. Light constrains numerous processes like primary production, visual predation (Langbehn & Varpe, 2017), or zooplankton depth in the Barents Sea (Aarflot, Aksnes, Opdal, Skjoldal, & Fiksen, 2019). It might change the limiting factors for boreal species entering the Barents Sea, as light conditions might be a particularly strong tradeoff at those latitudes (Poloczanska et al., 2016).…”
Section: Discussionmentioning
confidence: 99%